Research of descriptions of collinear aerial receiving system ADS-B by numeral methods - Харченко, В. П.; Барабанов, Ю. М.; Грехов, А. М.; Терещенко, Д. І. (Proceedings of National Aviation University (archive), 2013)
Calculations of electric field intensity and directional diagrammes for colinear antennas using a method of moments in the framework of two program complexes are carried out. Comparison has shown high level of results coincidence. The sample of the antenna which is used in operating system for reception of ADS-B signals from airborne transponders is constructed